2013
DOI: 10.4172/2329-6488.1000118
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Heart Rate Variability among Gutkha Chewers from a Rural Farming Background in India

Abstract: Background:Modernisation of life style has affected the population even in rural areas leading to addiction.Smokeless tobacco is presumed to be less of an evil by the rural folk. Gutkha addicts are likely to suffer from mental and physical exhaustion leading to stress. This is important in view of the prevailing socio-economic as well as the healthcare system available in any developing country. Therefore the present study is designed to measure heart rate variability among this special group of population.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 5 publications
2
5
0
Order By: Relevance
“…The results of this study suggest gutkha chewers experience an immediate rise in HR and rapid HRV response to acute tobacco exposure that do not persist 60 min following the end of exposure. [ 7 18 ] However, in agreement with some[ 29 ] but not all investigators, we were unable to show that the use of gutkha is associated with permanently raised HR and HRV variables. As is evident from this study, the hazards of gutkha are only partially known.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The results of this study suggest gutkha chewers experience an immediate rise in HR and rapid HRV response to acute tobacco exposure that do not persist 60 min following the end of exposure. [ 7 18 ] However, in agreement with some[ 29 ] but not all investigators, we were unable to show that the use of gutkha is associated with permanently raised HR and HRV variables. As is evident from this study, the hazards of gutkha are only partially known.…”
Section: Discussionsupporting
confidence: 84%
“…However, in a study by Pakkala et al . [ 29 ] Assessing the HRV among gutkha users, observed that the HRV parameters-time and frequency domain, showed significantly decreased values during the third month and sixth month recording after the exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HRV is a simple, economic, non invasive technique to evaluate sympatho-vagal balance and widely used method to assess autonomic functional status. [12] Time domain parameters of HRV [14] and Pakkala A et al [13] was found to be higher These findings emphasized sympathetic over activity in tobacco chewers. These results were comparable with Pakkala A et al [13] , Doss DSD et al [16] Mean of HF n.u.…”
Section: Discussionmentioning
confidence: 95%
“…[12] Time domain parameters of HRV [14] and Pakkala A et al [13] was found to be higher These findings emphasized sympathetic over activity in tobacco chewers. These results were comparable with Pakkala A et al [13] , Doss DSD et al [16] Mean of HF n.u. (%) in tobacco chewers was significantly lower (33.21±10.25) as compared to control subjects (57.44±8.44), (p˂0.001) and LF/HF ratio was found to be significantly higher in tobacco chewers (2.39±1.39) as compared to in control subjects (0.76±0.21), (p˂0.001).…”
Section: Discussionmentioning
confidence: 99%